Sensitivity of midnineteenth century tropospheric ozone to atmospheric chemistry-vegetation interactions - Hollaway, M.; Arnold, S.; Collins, Bill; Folberth, G.; Rap, A. (Wiley-Blackwell Publishing, 2017)
We use an Earth System model (HadGEM2-ES) to investigate the sensitivity of midnineteenth century tropospheric ozone to vegetation distribution and atmospheric chemistry-vegetation interaction processes. We conduct model experiments to isolate the response of midnineteenth century tropospheric ozone to vegetation cover changes between the 1860s and present day and to CO 2 -induced changes in isoprene emissions and dry deposition over the same period. Changes in vegetation distribution and CO 2 suppression of isoprene emissions between midnineteenth century and present day lead to decreases in global isoprene emissions of 19% and 21%, respectively. This results in increases in surface ozone over the continents of up to 2 ppbv and of 2-6 ppbv in the tropical upper troposphere. The effects of CO 2 increases on suppression of isoprene emissions and suppression of dry deposition to vegetation are small compared with the effects of vegetation cover change. Accounting for present-day climate in addition to present-day vegetation cover and atmospheric CO 2 concentrations leads to increases in surface ozone concentrations of up to 5 ppbv over the entire northern hemisphere (NH) and of up to 8 ppbv in the NH free troposphere, compared with a midnineteenth century control simulation. Ozone changes are dominated by the following: (1) the role of isoprene as an ozone sink in the low NO x midnineteenth century atmosphere and (2) the redistribution of NO x to remote regions and the free troposphere via PAN (peroxyacetyl nitrate) formed from isoprene oxidation. We estimate a tropospheric ozone radiative forcing of 0.264 W m -2 and a sensitivity in ozone radiative forcing to midnineteenth century to present-day vegetation cover change of -0.012 W m -2 .